Application of electroactive Au/aniline tetramer–graphene oxide composites as a highly efficient reusable catalyst. Issue 1 (22nd December 2020) - Lai, Guan-Hui; Chou, Yi-Chen; Huang, Bi-Sheng; Yang, Ta-I.; Tsai, Mei-Hui
Abstract : The stable and reusable Au/ATGO composites were prepared. Aniline tetramer not only modified GO but also can anchor Au NPs. The Au/ATGO composites as a catalyst exhibit good cycling stability. Abstract : This study proposes a cost-effective, energy-saving, and green process that uses π–π interactions to modify graphene oxide (GO), and the conjugate structure of aniline tetramer (AT) to enhance the dispersion of GO. Au/aniline tetramer–graphene oxide (Au/ATGO) composites were synthesized and applied as a catalyst in this study. The adsorption of AT on GO, via π–π interaction, formed ATGO composites. Subsequently, the amine group on ATGO was stably anchored on Au nanoparticles (Au NPs) to form Au/ATGO composites. The Au/ATGO composites were characterized and the electroactive properties determined by Fourier-transform infrared spectroscopy, X-ray photoelectron spectroscopy, transmission electron microscopy, and cyclic voltammetry. The Au/ATGO composites showed excellent performance and stability as catalysts when applied for the reduction of nitrophenol to aminophenol within 225 s and the rate constant was 0.02 s −1 . The activation energy for the reduction of 4-NP and 2-NP was 48.10 and 68.71 kJ mol −1, respectively. Following a recycling test repeated 20 times, the Au/ATGO composites maintained a conversion rate higher than 94%.